1996
DOI: 10.1111/j.1432-1033.1996.0724w.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilatory Sulfite Reductase Revisited

Abstract: Assimilatory sulfite reductase contains a sirohaem that is very weakly coupled to a [4Fe-4S] cubane, i.e. five iron atoms in total. Dissimilatory sulfite reductase is a complex system with 20 Fe atoms/a,p,y, hexamer. A recent revision of the purification procedure for the Desulfovibrio vulgaris dissimilatory enzyme has afforded a preparation of only 10 Fe atoms hexamer, this has led to the conclusion that the topology of prosthetic groups parallels that of the assimilatory system [Wolfe, €3. M., Lui, S. M. & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The specific activity of 48.2 nmol sulfite min − 1 mg − 1 was in the same range as that reported for dSir from various sulfate-reducing bacteria. 19,20,37 The diffraction data were phased with the MAD/SIRAS method using intrinsic iron atoms and a mercury derivative (Table 1). Structural refinement converged to R and R free values of 18.9% and 22.4%, respectively, in the resolution range of 10.0-2.0 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific activity of 48.2 nmol sulfite min − 1 mg − 1 was in the same range as that reported for dSir from various sulfate-reducing bacteria. 19,20,37 The diffraction data were phased with the MAD/SIRAS method using intrinsic iron atoms and a mercury derivative (Table 1). Structural refinement converged to R and R free values of 18.9% and 22.4%, respectively, in the resolution range of 10.0-2.0 Å.…”
Section: Resultsmentioning
confidence: 99%
“…17 Notably, assimilatory nitrite reductases, which convert nitrite to ammonia, also belong to the Sir family. 18 dSirs have been isolated from several sulfatereducing microorganisms, such as Desulfovibrio vulgaris, 19 Desulfovibrio desulfuricans, 20 Pyrobaculum islandicum, 21 and Archaeoglobus fulgidus, 22 and have been characterized with respect to their molecular, spectroscopic, and kinetic properties. The dSirs studied so far are composed of a heterotetrameric (αβ) 2 core complex and, depending on the organism, two additional small subunits, γ and δ, resulting in an (αβ) 2 γ n δ n multisubunit complex.…”
Section: Introductionmentioning
confidence: 99%
“…The aSiRs are monomeric and share low sequence similarity to dSiRs, which are large oligomeric proteins with a molecular mass in the order of 200 kDa and minimally composed of two different types of subunits in a a 2 b 2 arrangement (Schiffer et al, 2008). The number of cofactors in some proteins is also not clear with studies reporting from 2 to 4 sirohemes and 10-32 non-heme irons per a 2 b 2 module (Fauque et al, 1990;Marritt and Hagen, 1996;Moura et al, 1988;Pierik and Hagen, 1991;Wolfe et al, 1994). Although some authors propose that the cubane-siroheme cofactor arrangement of dSiRs is similar to that found in aSiRs (Moura et al, 1988;Wolfe et al, 1994), other authors have proposed the presence of higher nuclearity high-spin iron-sulfur clusters (Arendsen et al, 1993;Marritt and Hagen, 1996;Pierik and Hagen, 1991).…”
Section: Introductionmentioning
confidence: 96%
“…Cofactor quantification of dSiRs is quite disparate, with studies reporting from 2 to 4 sirohemes and from 10 to 32 non-heme irons per ␣ 2 ␤ 2 module (13,(17)(18)(19)(20). The nature of the catalytic cofactor has also been disputed, with some studies proposing a cubanesiroheme arrangement similar to that found in aSiRs (13,19) and other studies proposing the presence of higher nuclearity high spin iron-sulfur clusters (18,20,21). Finally, a most important and unresolved question is the nature of the physiological electron donor to dSiR.…”
mentioning
confidence: 99%